Analisis Kinerja Reksa Dana - Sri Wahyuni; Eko Purwanto (IPM2KPE, 2023)
The purpose of this research is to determine the effect of fund cash cash flow, fund size, fund age, and expense ratio variables on mutual fund performance. The population in this research is stock mutual fund products that are recorded and supervised by the OJK in 2019-2020. This research method is quantitative. The sample determination technique used purposive sampling, and produced 25 samples. The analysis technique in this study used multiple linear regression in SPSS software. The results showed that the calculated F test = 22.812 and a significance value (Sig.) = 0.000 <0.05. In conclusion, there is influence between the variables of fund cash flow, fund size, fund age, and expense ratio on the performance of mutual funds. Keywords: Expense Ratio, Fund Age, Fund Cash Flow, Fund Size, Mutual Fund Performance